Implementing Technology Invention For Micro, Small, And Medium-Sized Enterprises’ Human Resource Improvement: A Conceptual Model - Pemilia Sulistyowati; Heri Poerbantaro; Setia Iriyanto; Wahyudi Wahyudi; Sukamto Sukamto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia are now commercial organizations that can employ many people. There is a need for an efficient information system since there is a dearth of knowledge about marketing goals, despite the fact that many different MSME products have the potential to become high-quality exports. The more people there are who utilize the internet, the more probable it is that businesses will benefit from the increased competition. Therefore, the information system must provide MSMEs with access to digital marketing databases. To address this challenge, this piece presents a theoretical framework for applying technological innovation to the enhancement of human resources in micro, small, and medium-sized enterprises (MSME). Given the current shortcomings of HR improvement procedures in Indonesian MSMEs, this paper offers a comprehensive evaluation as a template for development in the field. In this article, we compare the current HR improvement practice in Indonesian MSMEs to national and international practices reported in the literatures reviewed and conclude that, in accordance with the national marketing information system of MSME owners, implementing technology invention has the potential to support HR improvement in Indonesian MSMEs.